2019
DOI: 10.1158/1538-7445.am2019-ct136
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT136: Evaluation of talazoparib in combination with irinotecan in early stage, high-risk HER2 negative breast cancer: Results from the I-SPY 2 TRIAL

Abstract: Background: I-SPY2 is a multicenter, Phase II trial using response-adaptive randomization within biomarker subtypes to evaluate novel agents as neoadjuvant therapy for high-risk at least T2N0 breast cancer. The primary endpoint is pathologic complete response (pCR) at surgery. The goal is to identify regimens that have ≥ 85% Bayesian predictive probability of success in a 300-patient phase 3 neoadjuvant trial defined by hormone-receptor (HR) and HER2 status, and MammaPrint (MP). Regimens may leave the trial fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Despite the small sample size, this trial showed an encouraging pCR rate of 53% and RCB-0/I of 63%, with a manageable safety profile. In the I-SPY2 trial, talazoparib combined with irinotecan for HER2-negative patients had limited activity beyond that seen with standard treatment ( 115 ).…”
Section: Targetable Molecular Pathwaysmentioning
confidence: 99%
“…Despite the small sample size, this trial showed an encouraging pCR rate of 53% and RCB-0/I of 63%, with a manageable safety profile. In the I-SPY2 trial, talazoparib combined with irinotecan for HER2-negative patients had limited activity beyond that seen with standard treatment ( 115 ).…”
Section: Targetable Molecular Pathwaysmentioning
confidence: 99%